Penerapan Simulasi Fisika Dalam Pembelajaran Sebagai Upaya Peningkatan Penguasaan Konsep, Afektif, dan Psikomotor Siswa Pada Pokok Bahasan Hukum Hooke dan Elastisitas di Kelas XI IPA 5 SMA Muhammadiyah Yogyakarta - Baroroh, Beni; Sajiman, Supardi Uki (Navigation Physics : Journal of Physics Education, 2023)
Physics learning that occurs in schools is directed at achieving learning objectives, namely in order to master the concepts of Physics and their interrelationships and be able to use scientific methods to solve the problems they face. Physics Education Technology (PhET) is a simulation of Physics experiments that can be used as an alternative in learning. The purpose of this study is to observe the learning process and examine the influence of the use of Physics simulation in improving the ability to understand Physics concepts in students. This research was conducted at SMA Muhammadiyah 2 Yogyakarta with the subject of research of grade XI Science 5 students consisting of 32 students in the first semester of the 2012/2013 academic year. While this type of research is classroom action research consisting of 3 cycles each cycle consisting of several stages, namely planning, action, observation and reflection. The data obtained in this study is in the form of evaluation results and conservation sheets of affective and psychomotor aspects in each cycle. The results showed that the application of simulation in learning can improve students' mastery of concepts. This is proven by the increase in cognitive, affective and psychomotor abilities of students.